Analysis of Adi Soemarmo Solo Airport Parking Payment System - Muqorobin Muqorobin; Rohmah Tulaila (International Journal of Computer and Information System (IJCIS), 2021)
The writing of the Semester Final Project with the title Analysis of the Parking Payment System for Adi Soemarmo Airport Solo was compiled based on the results of observations at the exit gate of Adi Soemarmo Airport Solo. Transactions on parking payments often cause problems due to several factors, especially the time or process is quite long because sometimes the money given is too large then the cashier takes too long to give change, besides that sometimes passengers do not prepare the money they want to pay in advance and often passengers pay in a situation of insufficient money and this causes queues or jams at the gate exit. The research objective given by the author later is to provide the best solution for airport parking payment systems. In addition to making it easier for passengers, this will greatly facilitate cashiers when carrying out work operations. This payment application system is called u-nik or electronic money. Where u-nik functions to transfer the money balance data contained in u-nik to a computer using a system called AINO. So that payments occur without spending additional cash. With the existence of non-cash payment transactions using the AINO system, it is hoped that it can facilitate and provide speed in making parking payment transactions without the need to carry cash.